Music Australia. - Music Australia (Erskineville, NSW : Music Australia, 2014)
"Music Australia is the only body in Australia devoted to music in its entirety. As a national umbrella body we are a passionate advocate, a sector focused researcher, a comprehensive information portal, a broker, and a provider of informed and relevant services. Our activities span music education, industry and community sectors to deliver campaigns, information, resources, engagement, and participation and demonstration projects."--About us
Title from title screen (viewed on 27 January 2015)
Mode of access: Available online. Address as at 25/3/15
Selected for archiving
Keywords: Music Australia; Associations, institutions, etc. -- Australia; Music -- Australia; Australian